Sleep disturbance in patients taking opioid medication for chronic back pain. (22nd August 2016) - Robertson, J. A.; Purple, R. J.; Cole, P.; Zaiwalla, Z.; Wulff, K.; Pattinson, K. T. S.
Summary: Poor sleep is an increasingly recognised problem with chronic pain and further increases the effect on daily function. To identify the relationship between chronic pain, opioid analgesia and sleep quality, this study investigated activity and sleep patterns in patients taking opioid and non‐opioid analgesia for chronic back pain. Thirty‐one participants (10 healthy controls, 21 patients with chronic pain: 6 on non‐opioid medication; 15 on opioid medication) were assessed using actigraphy, polysomnography and questionnaires. Patients with chronic pain subjectively reported significant sleep and wake disturbances as shown by decreased overall sleep quality (Pittsburgh Sleep Quality Index, p < 0.001), increased symptoms of insomnia (Insomnia Severity Index, p < 0.001) and increased fatigue (Fatigue Severity Scale, p = 0.002). They also spent increased time in bed (p = 0.016), took longer to get to sleep (p = 0.005) and had high interindividual variability in other measures of activity but no overall irregular rest‐activity pattern. Patients on high doses of opioids (> 100 mg morphine‐equivalent/day) demonstrated distinctly abnormal brain activity during sleep suggesting that polysomnography is necessary to detect sleep disturbance in this population in the absence of irregular rest‐activity behaviour. Night‐time sleep disturbance is common in individuals suffering from chronic pain and may be further exacerbated by opioid treatment. Considerations must be made regarding the appropriate use of combined actigraphy and miniaturised polysomnography for future population‐based studies. Abstract : ☛ CPD available athttp://www.learnataagbi.org